Abracadabra, or "I Create as I Speak": A Reanalysis of the First Verb in the Katumuwa Inscription in Light of Northwest Semitic and Hieroglyphic Luwian Parallels - Hogue, Timothy (Bulletin of ASOR, 2019)
Previous translations of the Katumuwa Inscription have either rendered the first verbal phrase (qnt ly) "I commissioned for myself," or "I acquired for myself." No scholars have yet defended the possibility that it simply means "I made." In fact, this is likely the case given the typical monumental rhetoric of Northwest Semitic and Hieroglyphic Luwian monumental inscriptions. In particular, a comparison with verbs of monumenting in Hieroglyphic Luwian inscriptions suggests that the monumenting phrase in the Katumuwa Inscription was calqued on a Luwian phrase. This difference is significant because it reveals an important aspect of the inscription's monumentality and the Syro-Anatolian conception of the stele. The stele that Katumuwa created was not understood merely as the inscribed object. Rather, the monument was the conjunction of material object, ritual engagement, and the resultant manifestation of the monument's commissioner. There was no monument apart from Katumuwa, whose voice was preserved in the inscription and whose presence could be reactivated through ritual. Therefore, Katumuwa did in fact "create" the stele as he spoke through it to his monument's users.